In Vitro Study of He, Ne Laser as an Agent for Melanin Formation to Vitiligo Treatment - Saja I. Dawood (Journal of Global Pharma Technology, 2018)
The standard curve for optimum concentration of different lymphocyte samples, were carried by ELISA using the procedure mention in the ELISA kit , using He-Ne laser for irradiated samples for different time, this study found there is a good correlation between the concentration of tyrosinase and optical density R2 =0.9615, by measuring the optical density of lymphocyte samples shows that for healthy person the concentration of tyrosinase more than patients but, the response for producing tyrosinase for patient is more than that for healthy person after using laser for different dose. This result indicates that laser radiation dose to enhance tyrosinase in lymphocyte to produce pigment cells. Keywords: Tyrosinase; Lymphocyte; Melanin; Vitiligo; He-Ne laser.